Legacies of Stalingrad : remembering the Eastern Front in Germany since 1945 - Morina, Christina 1976- (Cambridge University Press, 2011)
"Christina Morina's book examines the history of the Eastern Front war and its impact on German politics and society throughout the postwar period. She argues that the memory of the Eastern Front war was one of the most crucial and contested themes in each part of the divided Germany. Although the Holocaust gained the most prominent position in West German memory, official memory in East Germany centered on the war against the USSR. The book analyzes the ways in which these memories emerged in postwar German political culture during and after the Cold War, and how views of these events played a role in contemporary political debates. The analysis pays close attention to the biographies of the protagonists both during the war and after, drawing distinctions between the accepted, public memory of events and individual encounters with the war"--Provided by publisher